Immune Checkpoint Blockade sensitivity and Progression-Free Survival associates with baseline CD8+ T cell clone size and cytotoxicity - Watson, R; Tong, O; Taylor, C; Kumar Sharma, P; Verge De Los Aires, A; Mahe, E; Ruffieux, H; Nassiri, I; Middleton, M; Fairfax, B (bioRxiv, 2021)
This data forms the key input files for the analysis of single cell data as outlined in the publication titled: Immune Checkpoint Blockade sensitivity and Progression-Free Survival associates with baseline CD8+ T cell clone size and cytotoxicity. This is currently available as a pre-print on BioRXiv (DOI: https://doi.org/10.1101/2020.11.15.383786) and at the time of deposition is undergoing peer review.